Penerapan Pernyataan Standar Akuntansi Keuangan (PSAK) No. 27 pada Koperasi Pegawai Biotek LIPI Cibinong di Bogor - Jeffry . (STIE Binaniaga, 2010)
Preparation of Balance Sheet Biotech Employees Cooperative LIPI Cibinong not in accordance with Statement of Financial Accounting Standards (SFAS) No.. 27, so that the author made in accordance with SFAS No.. 27. Biotech Employees Cooperative LIPI should Cibinong, recruiting an employee who understands the preparation of financial statements that adhere to the Statement of Financial Accounting Standards (SFAS) No.. 27.